PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP ALOKASI BELANJA MODAL PADA KABUPATEN/KOTA PEMERINTAH PROVINSI ACEH - Ikhyanuddin Ikhyanuddin; Nanda Safitri (LPPM Universitas Bina Bangsa, 2022)
This research has been conducted to determine the effect of Regional Own-Source Revenues and Special Allocation Funds on the Capital Expenditures Allocation in Regencies/Cities in Aceh Province in 2014-2018. The data used in this study are secondary data in the form of the 2014-2018 Provincial Government APBK Reports consisting of own-source revenues realization data, and special allocation fund for capital expenditure realization data obtained through the website of the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia www.djpk.kemenkeu.go.id. The population in this study are 23 regencies/cities in Aceh Province consist of 18 regencies and 5 cities from 2014-2018. The data analysis method used is a multiple linear regression method with the help of SPSS (Statistical Package for Social Science) version 16.0. The results showed that partially, Own-Source Revenues has a significantly effect the allocation of capital expenditure of Regencies /Cities in the Aceh Province from 2014 to 2018. Partially, variable special allocation funds significantly influence the allocation of capital expenditure in the Regencies / Cities in the Aceh Province from 2014 to 2018 and simultaneously Own-Source Revenues and special allocation funds have a significant effect on capital expenditure allocations of Regencies/Cities in the Aceh Province from 2014 to 2018.